Effect of Sawdust Wood on some Mechanical properties of Recycled Polyethylene Terephthalate (RPET) (International Journal of Current Engineering and Technology, 2015)
The waste disposal is the main challenge in every country. The plastic usage is increasing day by day. Plastic wastes causes environmental pollution and depletion of landfill space . This study includes recycling of consumed transparent water bottles made from polyethylene terephthalate (PET) to prepare materials with properties valid for use in some construction field. This study includes preparing first set of recycled polyethylene terephthalate (RPET) with different melting temperature (180°C ,200°C ,220 °C , 240 °C) and mixing times (10,20,30,40,50 and 60 min) .50 minutes mixing time was chosen for mixing time .The second set of RPET composites filled with different weight Percentage of sawdust wood ( 10% , 20% ,30% , 40% , 50% and 60%) .Weight percentage 30% of sawdust wood was chosen for RPET/S.D.W composites . Samples for mechanical tests (compression, Charpy Impact , wear test ) for the first set of RPET and RPET/S.D.W composites were prepared . Eight samples (A , B , C , D , E, F, G , H ) from RPET and RPET/S.D.W composites were prepared for Compression test .The results showed that the samples A , B for recycled polyethylene terephthalate acquired maximum stress 31,26 N/mm2 and 30,09 N/mm2 respectively at melting temperature 180 °C , 200 °C and the samples did not fail and 33,10 N/mm2 for sample E of RPET/S.D.W composites at melting temperature 180 °C sample did not fail too in the same conditions with increase about 6.5 % when adding sawdust wood . Eight samples( I , J , K , L , M , N , O, P ) for RPET and RPET/S.D.W composites were prepared for Charpy impact test. The best results of impact resistance value 4.9 KJ/ m2 was found for sample I of RPET at melting temperature 180°C . Eight samples( Q , R , S , T , U , V , W, X )for RPET and RPET/S.D.W composites were prepared for wear test . Lowest wear rate value 0.99 × 10-7 gm / cm was observed for Sample Q prepared from RPET at melting temperature 180°C. It is concluded that RPET samples prepared at 180°C and 200°C and RPET/S.D.W composites prepared at 180°C show best results for compression test and concluded RPET samples prepared at 180°C show best results for charpy impact and wear test.
Keywords: Recycled PET; Sawdust Wood; Compression; Charpy Impact; Wear test